Severed Heads : the influence of Oscar Wilde on W.B. Yeats - Doody, Noreen (Trinity College (Dublin, Ireland). School of English, 2002)
This thesis is concerned with the literary influence of Oscar Wilde in the work of W.B. Yeats. Yeats was influenced by the images and intellect of Wilde. He assimilated Wilde’s concepts and symbols into his creative consciousness and developed them within his work until they became key factors within his creativity. In the thesis I explore the process of influence within this literary relationship in terms of its social, psychological, historical, imaginative and metaphysical aspects. The method of research includes an examination of manuscripts, typescripts and various published editions of single works and involved the study of historical data such as letters, journals, newspapers, texts. The argument also relies upon the application of Harold Bloom’s theory of poetry' as influence and the disruption of this theory in considering the ludic element at play in the process of influence.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin